Auditoría seguridad vial. ruta 50 RS 01 Apia - la Virginia, abscisas 25+000 a 16+000, tramo transversal las Animas – Bogotá. carretera transversal Central del Pacifico. Código 5003 (2021)
This document contains the development of the Road Safety Audit. Route 50 RS 01 Apia - La Virginia, abscissa 25 + 000 to 16 + 000, Transversal Section Las Animas - Bogotá. Central Pacific Highway. Code 5003 to the variables: barriers, geometric design of the road and signaling, to establish its condition in front of the road actors that circulate on it.